Regenerative Rehabilitation - Damayanti Tinduh (Indonesian Journal of Physical Medicine & Rehabilitation, 2018)
Rehabilitation is the health strategy which, based on WHO’s integrative model of functioning,disability and health applies and integrates approaches with the goal to enable persons with health conditions experiencing or likely to experience disability to achieve and maintain optimal functioning.The function status associated with physical activity is a health indicator and is the domain of quality of life. Human functioning is a major target of the rehabilitation program.